Advanced composite-based material selection for prosthetic socket application in developing countries. Issue 1 (1st January 2020) - Ramadhani, Gema Akbar; Susmartini, Susy; Herdiman, Lobes; Priadythama, Ilham
Abstract: World Health Organization (WHO) estimates that 35–40 million people in developing countries are amputees. One of the problems faced in developing countries is the lack of trained personnel in making prosthetic and to order a prosthetic limb abroad would not be practical and would require a large fee. Thus, amputees in developing countries rely on local prosthetic manufacturers. However, due to the lack of expertise, prosthetics that are manufactured in developing countries are only made of a fiber-like material or wood with a resin matrix. This mixture of material gave rise to problems for the amputees, due to its heavy nature. It has been found that there is a growing trend in the use of Advanced Composite Material (ACM) in several fields in developing countries. One of which is for the application of prosthetic sockets due to its strength to weight ratio and biocompatibility. This research will be carried out with the intent of selecting the most appropriate advanced composite-based material for a prosthetic arm socket. This research will also add additional research data by tensile and density test for each material alternatives referring to the ASTM standard. Based on the research that has been done, it is found that carbon kevlar among other things, has the highest strength among other alternatives (207.18 × 106 N/m2) and an adequately low density (1248.85 ± 0.098 kg/m3). Thus, carbon kevlar is selected as the most appropriate material because of its best performance value among other alternatives.